Hak-Hak Perempuan dalam Lensa Pemikiran Progresif K.H. Husein Muhammad - Nihayah, Rohatun; Wahidatunnisa, Ratna (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2025)
This research aims to answer the behaviors that are still mesdiscrimination of women, especially in women's rights that take one of the thoughts of Indonesian feminist figures, KH Husein Muhammad. First, how are women's rights in the view of Islam. Second, how does KH Husein Muhammad think about women's rights in Islam using the theory of gender equality.The method used in this research is qualitative with a descriptive approach that is library research. The data obtained in this study are from books by KH Husein Muhammad as well as interviews with him and there are also supporting sources in the form of articles or previous research that are not much different from the discussion of women's rights. In the perspective of gender equality theory, according to KH Husein Muhammad, women and men have the same potential so that women and men can get the same rights. Women are also not always inferior to men, be it in terms of reason, ability, courage, and so on. And women also have the right to refuse their husband's wishes if it could be dangerous or will have a bad impact on themselves with reasons allowed by religion